2016
DOI: 10.5978/islsm.16-or-18
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment comparison by application of diamond bur and Er,Cr:YSGG at different powers: morphological and mechanical evaluation

Abstract: This study evaluated the micro-tensile bond strength of new and previous composite resin restorations after surface treatment with diamond bur and Er,Cr:YSGG laser at different power settings (2,3 and 4 W). Micro-hybride composite resin was inserted in metallic mold 5 ×5 ×15 mm and cured for 40 sec according to manufacturer's instruction.12 blocks were made. The bonded surfaces of the 12 blocks so obtained were subsequently ground using Silicon Carbide papers 1200 grit, for 15 seconds under running water. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The Er,Cr:YSGG laser have been introduced into restorative dentistry owing to its capabilities in surface roughness of different dental materials to enhance the bond strength [26,27,[33][34][35], the SEM images of the hybrid resin ceramic showed that acid etching exposed filler particles to form irregular surface with retentive micropores that may improve the mechanical interlocking with resin cement [50] as shown in Figure 6 (A) and in Figure 6 For the failure mode analysis, group RC-C was mainly cohesive failure in the substrate and for groups RC-L1 and RC-L2 showed cohesive, mixed and adhesive failures, denoting stronger micromechanical bond between Vita Enamic and resin cement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Er,Cr:YSGG laser have been introduced into restorative dentistry owing to its capabilities in surface roughness of different dental materials to enhance the bond strength [26,27,[33][34][35], the SEM images of the hybrid resin ceramic showed that acid etching exposed filler particles to form irregular surface with retentive micropores that may improve the mechanical interlocking with resin cement [50] as shown in Figure 6 (A) and in Figure 6 For the failure mode analysis, group RC-C was mainly cohesive failure in the substrate and for groups RC-L1 and RC-L2 showed cohesive, mixed and adhesive failures, denoting stronger micromechanical bond between Vita Enamic and resin cement.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CAD/CAM hybrid resin ceramics, studies were published on the impact of different surface treatments of indirect restorations on its bond strength to resin cement [29][30]. Recently, Erbium lasers have been established efficacious on composite resin restorations such as composite inlays, onlays, etc… as surface treatment for enhancing bond strength [31][32][33][34]. On the contrary, the efficacy of Er,Cr:YSGG laser irradiation on hybrid resin ceramics is yet to be proven due to the shortage of related studies [35].…”
Section: Palavras-chavementioning
confidence: 99%